Monolithic solid–electrolyte interphases formed in fluorinated orthoformate-based electrolytes minimize Li depletion and pulverization - Cao, Xia; Ren, Xiaodi; Zou, Lianfeng; Engelhard, Mark H.; Huang, William; Wang, Hansen; Matthews, Bethany E.; Lee, Hongkyung; Niu, Chaojiang; Arey, Bruce W.; Cui, Yi; Wang, Chongmin; et al. (Nature energy, 2019)
Lithium (Li) pulverization and associated large volume expansion during cycling is one of the most critical barriers for the safe operation of Li-metal batteries. Here, we report an approach to minimize the Li pulverization using an electrolyte based on a fluorinated orthoformate solvent. The solid–electrolyte interphase (SEI) formed in this electrolyte clearly exhibits a monolithic feature, which is in sharp contrast with the widely reported mosaic- or multilayer-type SEIs that are not homogeneous and could lead to uneven Li stripping/plating and fast Li and electrolyte depletion over cycling. The highly homogeneous and amorphous SEI not only prevents dendritic Li formation, but also minimizes Li loss and volumetric expansion. Furthermore, this new electrolyte strongly suppresses the phase transformation of the LiNi 0.8 Co 0.1 Mn 0.1 O 2 cathode (from layered structure to rock salt) and stabilizes its structure. Tests of high-voltage Li||NMC811 cells show long-term cycling stability and high rate capability, as well as reduced safety concerns. Parasitic reactions between Li metal and electrolytes need to be mitigated in Li-metal batteries. Here, the authors report the use of a fluorinated orthoformate-based electrolyte, leading to a monolithic solid–electrolyte interphase and subsequently a high-performance Li-metal battery.